KRAS targeting antibody synergizes anti-cancer activity of gemcitabine against pancreatic cancer - Kang, Yeo Wool; Lee, Ji Eun; Jung, Kyung Hee; Son, Mi Kwon; Shin, Seung Min; Kim, Soo Jung; Fang, Zhenghuan; Yan, Hong Hua; Park, Jung Hee; Han, Boreum; Cheon, Min Ji; Woo, Min Gyu; et al. (Cancer Letters, 2018)
Pancreatic cancer exhibits an oncogenic KRAS mutation rate of ∼90%. Despite research and drug development efforts focused on KRAS, no targeted therapy has been clinically approved for the treatment of pancreatic cancer with KRAS mutation. Also, the efficacy of gemcitabine is poor due to rapidly acquired resistance. We developed RT11-i antibody, which directly targets the intracellularly activated GTP-bound form of oncogenic RAS mutants. Here, we investigated the combined effects of RT11-i and gemcitabine in vitro and in vivo, and the mechanism involved. RT11-i significantly sensitized pancreatic cancer cells to gemcitabine. Also, the co-treatment synergistically inhibited angiogenesis, migration, and invasion, and showed synergistic anticancer activity by inhibiting the RAF/MEK/ERK or PI3K/AKT pathways. Furthermore, co-treatment inhibited endothelial barrier disruption in tumor vessels, which is a critical step in vascular leakiness of metastasis, and improved vessel structural stability. Importantly, co-treatment significantly suppressed tumor growth in an orthotopic tumor model. Taken together, our findings show that RT11-i synergistically increased the antitumor activity of gemcitabine by inhibiting RAS downstream signaling, which suggests RT11-i and gemcitabine be viewed a potential combination treatment option for pancreatic cancer patients with KRAS mutation.
Keywords: Animals; Antibodies; Antineoplastic Combined Chemotherapy Protocols; Carcinoma, Pancreatic Ductal; Cell Line, Tumor; Deoxycytidine; Drug Synergism; Humans; Mice, Inbred BALB C; Mice, Nude; Mutation; Pancreatic Neoplasms; Proto-Oncogene Proteins p21(ras); Signal Transduction; Tumor Burden; Xenograft Model Antitumor Assays; Antibody drug; KRAS mutation; Pancreatic cancer